2017
DOI: 10.1016/j.appdev.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Competitive classroom norms and exclusion of children with academic and behavior difficulties

Abstract: We investigated effects of classroom-level norms and individual competitive attitudes on children's exclusion of hypothetical peers with behavior or academic difficulties. Upper elementary school children (N = 1,009) from Switzerland were presented with four scenarios about social exclusion at two time points (fifth and sixth grade). These scenarios varied according to difficulty type of exclusion target (low-achieving vs. hyperactive) and context of exclusion (academic vs. social). Multilevel analyses reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 59 publications
2
19
0
3
Order By: Relevance
“…In addition to group norms, the positive effects of cross‐group friendships can be explained by the increased significance of affective characteristics of friendships during this period (Bukowski et al., ; Newcomb & Bagwell, ). As the current study investigated two underlying processes through which adolescents with cross‐group friendships develop positive intergroup attitudes (i.e., intergroup trust and sympathy), this study provides a better understanding of how prejudice can be reduced during this sensitive period of increased academic pressure that may pose conflicting demands for adolescents: belonging to high achieving peer groups or being inclusive toward students with low academic achievement (Gasser et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to group norms, the positive effects of cross‐group friendships can be explained by the increased significance of affective characteristics of friendships during this period (Bukowski et al., ; Newcomb & Bagwell, ). As the current study investigated two underlying processes through which adolescents with cross‐group friendships develop positive intergroup attitudes (i.e., intergroup trust and sympathy), this study provides a better understanding of how prejudice can be reduced during this sensitive period of increased academic pressure that may pose conflicting demands for adolescents: belonging to high achieving peer groups or being inclusive toward students with low academic achievement (Gasser et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the findings of our study, adolescents may have been more likely to exclude a hypothetical student with low academic achievement, as the inclusion of this student might have impeded effective academic group functioning. Findings from a recent study suggest that the context of increased academic pressure may even increase adolescents' decisions to exclude individuals with low academic achievement, as their low academic performance does not conform to group norms of well‐performing groups (Gasser, Grütter, Torchetti, & Buholzer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, contextual factors might also explain some variance. As noted in the introduction, class size (Park et al, 2014) and class climate (Gasser et al, 2017;Krawinkel et al, 2017) can be used to further explain the variance of aspects of social participation. Finally, successful social participation of all students may only be possible in school settings that provide the necessary support and resources (Borg et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Gender (DeBoer et al, 2012) and psychomotor clumsiness (Ruiz-Pérez et al, 2018) also play an important role in social acceptance and interactions. Furthermore, research also suggests that class variables matter in social inclusion (e.g., class climate: Gasser et al, 2017;heterogeneity: Grütter et al, 2014;and class size: Park et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lazega et al (2016) indicated that workers with emotional labor load were mostly the frontline staff in an organization, who had to cover or control personal emotion at work and present emotional behaviors requested by the organization in order to result in better customer satisfaction. Gasser et al (2017) regarded emotional labor as individual perceived organizational emotional expression norms and work-focused emotional labor of individual emotional complexity presented in public occasions, under organizational norms and compensation systems as well as employee-focused emotional labor of individual surface emotional acting for adapting to work requirements and the required internalization of deep emotional. Nieto & Gonzalez-Alvarez (2016) revealed emotional labor as the control of personal emotion and the expression of specifi c emotion requested by the organization in order to achieve organizational benefi ts and objectives.…”
Section: Emotional Labormentioning
confidence: 99%